+0  
 
0
197
1
avatar+559 

What is the recursive rule for the sequence?

 

 May 1, 2018
 #1
avatar+21869 
0

What is the recursive rule for the sequence?

 

 

\(\text{arithmetical sequence: $\\$ $a_n-a_{n-1} = d = 6 \\$ } \)

 

\(\text{arithmetical sequence: $\\$ $a_n = a_1 + (n-1)d \\$ } \\ \text{ $a_1 = 39 $ and $d=6 $ } \)

 

\(\begin{array}{|rcll|} \hline a_n &=& a_1 + (n-1)d \\ a_n &=& 39 + (n-1)6 \\ a_n &=& 39+6n -6 \\ \mathbf{a_n} & \mathbf{=} & \mathbf{33+6n} \\ \hline \end{array}\)

 

laugh

 May 2, 2018

19 Online Users

avatar
avatar